Cognitive and Functional Trajectories in Prediagnostic Parkinson's Disease. (20th December 2022) - Bock, Meredith A; Vittinghoff, Eric; Bahorik, Amber L; Leng, Yue; Yaffe, Kristine
Abstract: Background: Cognitive and functional decline is typically considered a late manifestation of Parkinson's Disease (PD). However, impactful non‐motor symptoms can occur prior to the typical motor symptoms due to prodromal neurodegeneration. Few studies have investigated prediagnostic trajectories of cognition and function. Method: We studied 15, 390 participants from two prospective cohort studies of community‐dwelling elders (one of men and one of women) followed up to 20 years. PD was repeatedly ascertained by self‐reported physician diagnosis over follow‐up. We excluded individuals with prevalent PD at baseline (n = 152). Global cognition (Modified Mini‐Mental State Examination or the Mini‐Mental Status Exam), executive function (Trails B), and functional status (interviewer administered IADL and physical function questionnaire) were repeatedly evaluated in both studies. Raw scores were z‐transformed to mean 0 and standard deviation 1. We estimated the associations of PD diagnosis with rates of change in cognition and function before and after PD diagnosis compared to healthy older adults using mixed‐effects models adjusted for age, education, race, body mass index, smoking, alcohol use, depression, and cardiovascular risk factors. Result: Over follow‐up, 297 individuals developed incident PD (168 men and 129 women). Interactions between the terms in our model and sex were statistically significant for all three outcomes (p<0.001 for all), so we stratified results by sex. Compared to older men without PD, men who developed PD exhibited faster decline in global cognition (0.04 SD difference in annual change, p<0.001), executive function (0.05 SD difference, p<0.001), and functional status (0.06 SD difference, p<0.001) in the prediagnostic period. Women who developed PD compared to women without PD displayed faster decline in executive function (0.02 SD difference, p = 0.006) and functional status in the prediagnostic period (0.07 SD difference, p<0.001). Conclusion: Individuals who develop PD exhibit decline in executive function and functional status during the prediagnostic phase that exceeds rates associated with normal aging. Men exhibit more cognitive decline prior to PD diagnosis compared to women. Better understanding the prodromal phase of PD may enable earlier diagnosis and open a window for the management of non‐motor symptoms to improve quality of life and facilitate the development of future neuroprotective treatments.